2005
DOI: 10.2174/138920005774330639
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Enzymes Mechanism Based Inhibitors: Common Sub-Structures and Reactivity

Abstract: The inhibition of human cytochrome P450s (CYPs) is one of the most common mechanisms which can lead to drug-drug interactions. The inhibition of CYPs can be reversible (competitive or non-competitive) or irreversible. Irreversible inhibition usually derives from activation of a drug by CYPs into a reactive metabolite, which tightly binds to the enzyme active site, leading to a long lasting inactivation. This process is called "mechanism based inhibition" or "suicide inhibition". The irreversible inactivation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(122 citation statements)
references
References 17 publications
2
118
0
2
Order By: Relevance
“…At the opposite, the affinity of 5 for CYP2J2 seems to be higher than that of 13, as suggested by the K I (0.45 ± 0.05 and 2.9 ± 0.2 μM respectively, Table 4) and IC 50 values (0.4 ± 0.1 and 6.7 ± 2 μM, respectively, Table 1) found for these compounds. Table 4 also compares kinetic constants reported for other CYP mechanism-based inactivators [56]. It indicates that 5 and 13 are reasonably efficient mechanism-based inactivators of CYP2J2, as judged from their k inact /K I values.…”
Section: Kinetics Of Cyp2j2 Inactivation By 5 and 13-mentioning
confidence: 92%
See 1 more Smart Citation
“…At the opposite, the affinity of 5 for CYP2J2 seems to be higher than that of 13, as suggested by the K I (0.45 ± 0.05 and 2.9 ± 0.2 μM respectively, Table 4) and IC 50 values (0.4 ± 0.1 and 6.7 ± 2 μM, respectively, Table 1) found for these compounds. Table 4 also compares kinetic constants reported for other CYP mechanism-based inactivators [56]. It indicates that 5 and 13 are reasonably efficient mechanism-based inactivators of CYP2J2, as judged from their k inact /K I values.…”
Section: Kinetics Of Cyp2j2 Inactivation By 5 and 13-mentioning
confidence: 92%
“…Most of them derive from terfenadone by replacement of its t-butyl group with various R groups of different size and polarity. This includes R groups bearing chemical functions well known to lead to suicide inactivation of cytochrome P450 after in situ oxidation [52][53][54][55][56]. This is the case of the terminal double bond of compound 5, of the CHF 2 function of compound 12, and of the benzo-1,3-dioxole function of compound 13 ( Table 1).…”
Section: Synthesis Of Three Series Of Derivatives Of Terfenadone Dehmentioning
confidence: 99%
“…The recently established CYP phenotyping reaction focuses on determining the CYP isoform involved in the metabolism of a given drug [12]; The list of phenotyped compounds continues to grow [13]. Before conducting CYP phenotyping, however, it is important first to define the predominant clearance mechanisms for the investigational drug in question.…”
Section: Metabolism By Microsomesmentioning
confidence: 99%
“…This process is called "mechanism based inhibition" or "suicide inhibition". Fontana et al presented a general and systematic review with this regard [13].…”
Section: Chemical and Antibody Inhibitionmentioning
confidence: 99%
“…A major concern with acetylenes in potential drugs is the possibility of chemical or metabolic reactivity (Milbank et al, 2007). Terminal acetylenes are well known to be mechanism-based CYP-inactivators (Testa & Jenner, 1981) and there is an increasing body of information suggesting that internal acetylenes can be activated by CYPs (Fontana et al, 2005;Foroozesh et al, 1997;Shimada et al, 2007) or even undergo uncatalyzed addition of glutathione Mutlib et al, 1999). Mutlib et al reported that incubation of MPEP with triple-labeled glutathione gave compounds with molecular weights and fragmentations consistent with both activated and unactivated addition of GSH to the alkyne (Mutlib et al, 2005).…”
Section: Allosteric Modulators and Radiotracers For Mglur5mentioning
confidence: 99%